Major and minor discordance in the diagnosis of postmenopausal osteoporosis among Indian women using hip and spine dual-energy X-ray absorptiometry - Meeta Singh; Navneet Magon; Tanvir Singh (Wolters Kluwer Medknow Publications, 2012)
Objective: To determine discordance in the diagnosis of osteoporosis among postmenopausal Indian women using hip and spine Dual-energy X-ray Absorptiometry. Materials and Methods: The study included postmenopausal women who underwent bone mineral densitometry (BMD) for suspected osteoporosis at a referral hospital at Hyderabad, India. The BMD measures at the hip and spine were used to derive T-scores and to determine the prevalence of discordance. Factors potentially associated with discordance were explored in univariate and a multivariate regression model. Results: The mean age of the 348 postmenopausal women in the study was 53.62 ± 8.94 years (median 53.00 years, range 27.00 to 84.00 years). Major discordance was seen in 16.67% (95% confidence intervals [CI]: 12.73, 20.60) of the study population and minor discordance in 34.48% (95% CI: 29.46, 39.50%) of the study population. Age >50 years (adjusted odds ratios [OR]: 2.60, 95% CI: 1.24, 5.46, P value = 0.01), premature menopause (adjusted OR: 2.94, 95% CI: 1.27, 6.81, P value = 0.03), and multiple pregnancies (adjusted OR: 2.64, 95% CI: 1.28, 5.41, P value = 0.008) were found to be significantly associated with major discordance. Conclusions: The large prevalence of discordance may reflect the differences in osteoporosis in different populations and suggests the need to redefine ranges and risk factors used for the diagnosis of osteoporosis in India.